The Power of Connection: Understanding Kitty Pong’s Social Ambitions in Kevin Kwan’s China Rich Girlfriend (2015) - Mailani Salsabila; Puji Laksono (Metaphor, 2025)
This study is aimed to analyze : 1) the motivations influencing Kitty Pong to becoming a social climber in China Rich Girlfriend (2015), 2) how the power of connection in China Rich Girlfriend (2015) can be used to gain high social status. This research uses a qualitative method to analyze the novel China Rich Girlfriend (2015) written by Kevin Kwan as the object of study. The data collection methods include reading, identifying, and selecting. The researcher utilizes A. H. Maslow’s theory of the hierarchy of needs, Pierre Bourdieu’s theory of social capital, and John Storey’s theory of consumption to analyze the data through steps of classifying, analyzing, and interpreting. The result of this research shows that the motivations influencing Kitty Pong to becoming a social climber in China Rich Girlfriend (2015) including want to acquire high status, recognized by influential people, accepted by the society, and acquire power. The power of connection in China Rich Girlfriend (2015) that Kitty Pong can use to gain high social status including economic, cultural, and social capital, also cultural fields, and habitus. The impacts of a social climber in China Rich Girlfriend (2015) including impacts in economic, psychological, and social life.